Progressive Law Analysis of Injustice in Asset Value Requirements for Construction Services - Misno Misno; Ahmad Ahmad; Istiqomah Istiqomah; Aris Gumilar (Indonesian Journal of Law and Policy Studies, 2024)
The Minister of Public Works and Housing Regulation No. 8 of 2022 establishes an asset value requirement of IDR 5 billion for M2 qualification in the installation sector, consequently marginalizing 88% of small-scale construction service enterprises. This research employs qualitative methodologies incorporating juridical-normative and juridical-empirical approaches to analyze the regulatory injustice through the lens of Satjipto Rahardjo's Progressive Law Theory. Data were collected through in-depth interviews with 25 respondents representing diverse stakeholder categories. The findings demonstrate that asset value requirements lack adequate philosophical, juridical, and sociological foundations for the installation sector, which functions as a knowledge intensive industry. The regulatory implementation engenders distributive, procedural, and interactional injustice, contradicting the fundamental principle of "law for humanity." The regulation has resulted in the displacement of 131,000 employment positions and a 64.3% reduction in government project accessibility, without establishing any empirically validated correlation between asset value and technical competency. This study recommends an implementation moratorium and the development of competency-based qualification models more consonant with the installation industry's distinctive characteristics.